2013
DOI: 10.3892/or.2013.2417
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ERas gene in gastric cancer cells

Abstract: As a novel member of the Ras family, ERas, found in murine embryonic stem (ES) cells in 2003, was considered a pseudogene. To date, there are a few reports on the relationship between ERas and tumors. It was recently suggested that ERas could affect gastric carcinoma (GC) metastasis, but no significant relationship was found with tumor proliferation. Since ERas plays an important role in tumor-like growth of ES cells subcutaneously injected into nude mice, we hypothesized that ERas plays a role in tumor prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous work has shown that ERas activates the PI3K pathway, but not the MAPK pathway, when expressed in mouse ES cells or human cell lines (39,40). Thus, we examined AKT, ERK, and MEK phosphorylation in 451Lu cells overexpressing ERAS and found robust AKT phosphorylation, whereas MAPK activity was unaffected (Fig.…”
Section: −08mentioning
confidence: 88%
See 1 more Smart Citation
“…Previous work has shown that ERas activates the PI3K pathway, but not the MAPK pathway, when expressed in mouse ES cells or human cell lines (39,40). Thus, we examined AKT, ERK, and MEK phosphorylation in 451Lu cells overexpressing ERAS and found robust AKT phosphorylation, whereas MAPK activity was unaffected (Fig.…”
Section: −08mentioning
confidence: 88%
“…It was first identified as a potent oncogene in murine ES cells because of its ability to promote constitutive activation of the PI3K pathway (39). More recently, human ERAS has been proposed to play a role in cancers of the gastrointestinal tract (40,56), and in vitro studies have suggested a role in the resistance of cell lines to chemotherapeutics (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…WNT9A is a member of WNT gene family and correlated with oncogenesis [21]. ERAS may be involved in the pathogenesis and chemotherapy resistance of some types of cancers [22, 23]. Our study indicated their role in SCLC oncogenesis where TP53 and RB1 inactivation are absent.…”
Section: Discussionmentioning
confidence: 64%
“…Pseudogenes, which are highly homologous with their parental genes, are ideal candidates to sustain the expression of their parental genes by serving as competing endogenous RNAs ( ceRNAs ) which compete for the binding site of the same mRNAs [16, 28]. In addition, some could regulate the expression of functional genes by producing endogenous small interference RNAs ( siRNAs ) [29, 30] and antisense RNAs ( asRNAs ) [31, 32], and some even could encode functional proteins [33, 34]. It is speculated that pseudogenes can be the supplement to their parental genes via gene mutation in a particular position.…”
Section: Discussionmentioning
confidence: 99%